Evidências do lineamento transbrasiliano na região nordeste de Mato Grosso do Sul : aspectos lito-estruturais e aerogeofísicos (magnetometria e gravimetria) - Campos, Francisco Abel Pompeu de (2015)
The Transbrasiliano Lineament is the most important continental scale fault zone recognized in Brazil, crosscuts the South American platform in a NE-SW direction, influencing several domains in this platform since the brasiliano, including the Paraná Basin development and structuring. There are at least three reactivations recognized since the Devonian, the latter related to the opening of the South Atlantic in Cretaceous with generation of the Serra Geral magmatism associated with the Paraná Basin. Qualitative interpretations of magnetic lineaments suggest magnetic discontinuity related to the main trend of the Transbrasiliano Lineament concealed by Paraná Basin in the northeastern of Mato Grosso do Sul state. The results of the Matched Filtering application shows three magnetometric levels with their respective depths where its vertical continuity reaches at least 25 km. High-frequency fields can be related to the magmatism in the shallow level of this filtering in the eastern portion of the study area, with no indication of the presence in the central and western portion of the area. Is associated with absence of the Serra Geral magmatism in this region faults characteristic of extensional nature in a standard horst type, with subsequent recurring erosive character of river activities. An oblique system intersects the main discontinuities moving them in a structural rearrangement of the blocks evidenced in the geophysical data and field control, with joints imposed on magmatism with cretaceous age.